The discourse of conflict : an appraisal analysis of newspaper genres in English and Runyankore-Rukiga in Uganda (2001-2010) - Mugumya, Levis (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.